Plasma levels of H‐ and L‐ficolin are increased in axial spondyloarthritis: improvement of disease identification. (1st October 2019) - Troldborg, A.; Thiel, S.; Mistegaard, C. E.; Hansen, A.; Korsholm, T.‐L.; Stengaard‐Pedersen, K.; Loft, A. G.
Summary: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease that primarily affects the axial skeleton. A predominance of innate versus adaptive immune responses have been reported in axSpA, indicating a prominent autoinflammatory component of the disease. Little is known about the lectin pathway proteins (LPPs) of the complement system in relation to axSpA. We have investigated LPPs in patients with axSpA and control individuals. Plasma samples were obtained from a cross‐sectional cohort of 120 patients with a clinical diagnosis of axSpA and from 144 age‐ and gender‐matched controls. The plasma concentrations of 11 LPPs were measured, using sandwich‐type time‐resolved immunofluorometric assays in patients and controls, and related to clinical diagnosis and disease activity. Three LPPs [H‐ficolin (ficolin‐3), L‐ficolin (ficolin‐2) and collectin liver 1 (CL‐L1)] were significantly higher in axSpA patients than in controls ( P < 0·0001) and one LPP, collectin kidney 1 (CL‐K1), was significantly lower ( P < 0·0001). Further, combining H‐ or L‐ficolin concentrations above the 75th percentile of the respective H‐ or L‐ficolin concentration measured in controls with human leucocyte antigen (HLA)‐B27 positivity yielded axSpA diagnostic specificities of 99/99% and positive likelihood ratios of 68/62, respectively. H‐ficolin and L‐ficolin plasma concentrations were found to be elevated in axSpA patients regardless of time since diagnosis. H‐ficolin and L‐ficolin may represent diagnostic biomarkers for patients with axSpA and should be further evaluated. Our results showed no association between disease activity and the measured LPP concentrations. This result might be due to the cross‐sectional design, and should be further investigated. Abstract : We present the first report of elevated plasma levels of lectin pathway proteins in axial spondyloarthritis. An elevated level of H‐ or L‐ficolin ficolin improves the diagnostic specificity of HLA‐B27 positivity and may be new promising biomarkers for the diagnosis of axial spondyloarthritis